Prospects for the Development of Halal, Thoyib, and Hygienic Food Production During the New Normal Covid-19 Period as Supporting Pillars of National Food Security - Muhamad Muslih; Ferina Ardhi C (Unram Law Review, 2021)
The background of this research is that the government claims that the Covid-19 pandemic has actually increased consumer awareness on the consumption of halal products, ranging from food products, beverages, traveling, to cosmetics. The government also seeks to increase awareness of the development of halal and thoyib products. This is supported by the data the authors obtained from various literatures. The legal issues raised in this study are formulated into several problem formulations, namely whether regulations and supervision regarding the development of halal products in Indonesia can meet all sharia principles regarding halal, toyib, and hygienic considering that Indonesia is a muslim majority? How is the process of developing the ability of producers and SMEs in Indonesia in developing halal products? How is the category of halal certification for products in Indonesia as one of the important categories for food products to meet the principles of halal and thoyib? Based on this formulation, this study analyzes the regulation and supervision of halal product development, halal product development process, and categories of halal, thoyib, and hygienic food products that are in accordance with LPPOM MUI halal food standards so that these products can be certified as halal products. The purpose of this research is to be able to develop halal, thoyib, and hygienic food production during the Covid-19 period as a supporting pillar of national food security. The method used is the normative juridical research method. This research is descriptive research with the source of the data used in this study was obtained from library research. The results of this study, namely the data that the authors obtained indicate that there has been an increase in public awareness on the consumption of halal products, ranging from food products, beverages, traveling, to cosmetics during the Covid-19 period. In line with this, the government also continues to strive to increase awareness of the development of halal and thoyib products.